Targeting mitophagy for depression amelioration: a novel therapeutic strategy - Xu, Wangjun; Gao, Weiping; Guo, Yukun; Xue, Feng; Di, Lulu; Fang, Shaojie; Fan, Linlin; He, Yangyang; Zhou, Yunfeng; Xie, Xinmei; Pang, Xiaobin (Frontiers in Neuroscience, 2023)
Major depressive disorder is a global psychiatric disorder characterized by persistent low mood and anhedonia, which seriously jeopardizes the physical and mental well-being of individuals affected. Although various hypotheses have been proposed to explicate the etiology of depression, the precise pathogenesis and efficacious treatment of this disorder remain elusive. Mitochondria, as the primary organelle responsible for cellular energy production, have the ability to meet the fundamental energy demands of the brain. Research has found that the accumulation of damaged mitochondria is associated with the onset of depression. Mitophagy is a type of cellular autophagy that specifically targets and removes excess or damaged mitochondria. Emerging evidence showed that mitophagy dysfunction was involved in the progression of depression, and several pharmacological interventions that stimulating mitophagy exerted excellent antidepressant actions. We provided an overview of updated advancements on the regulatory mechanism of mitophagy and the mitophagy abnormality in depressed patients and animals, as well as in cell model of depression. Meanwhile, various therapeutic strategies to restore mitophagy for depression alleviation were also discussion in this review.